Fruit and seed biometry and germination of Victoria amazonica (Poepp.) J.C. Sowerby (Nymphaeaceae) from the Pantanal floodplain - Luiz Ricardo dos Santos Tozin (Acta Scientiarum : Biological Sciences, 2016)
Numerous plant species are easily established in the wide flood plains of the Pantanal wetlands due to the environmental heterogeneity. The aquatic macrophytes excel in permanently flooded areas, particularly Nymphaeaceae species. Victoria amazonica, popularly known as the vitória-régia, is hallmarked for its beauty. However, the biology and conditions necessary for the seed germination of this flowering plant remain unknown. In the present study, the fruit and seed morphology and biometry were described and the seed germination was evaluated under different abiotic conditions. To this end, mature fruits of V. amazonica were collected from the bays near Paraguay River in the south Pantanal floodplain. The fruits and seeds were described and measured using digital caliper. Intact and mechanically scarified seeds were germinated under different temperature, light and substratum conditions, and the initial development was described. The fruits measured 67.5 x 119.7 mm in size and contained 100-700 seeds. The average seed measured 10.6 mm in length and 9.8 mm in width. The highest germination occurred at 25oC, independent of the light condition. The seeds were considered neutral photoblastic. The seedlings showed heterophylly, and the main root was degenerated, forming adventitious roots. Morphological differences were observed in seedlings developed under different light conditions.